Bennett’s Fracture - Ozdemir, Serdar; Taşlıdere, Bahadır; TAŞLIDERE, BAHADIR; Ozkan, Abuzer (My University, 2022)
A 24-year-old female patient applied to our clinic with the complaint of falling from a ladder. She had no history of illness or drug use. In the anamnesis, it was learned that he fell after his foot slipped. Vital signs were stable. On physical examination, there was no feature other than tenderness in the proximal left 1st metacarpal bone. Fracture fragment was observed in the proximal of 1st metacarpal bone in conventional radiography imaging (figure 1). A plaster cast was applied after closed reduction. Conservative treatment was planned, and the patient was discharged. Bennett’s fracture is the retention of the bone to which the beak ligament is attached, and the dorsoradial and proximal subluxation of the base of the metacarpal detached from this part (1). Key features are intra- Conflict of interest: Authors declare no conflict of interest. REFERENCES articular fracture, oblique fracture pattern, and volar- dorsal fragment. The medial small piece remains in place and maintains its relationship with the second finger via the volar oblique ligament (Beak ligament). However, the fractured metacarpal body is displaced proximally and laterally by the abductor pollicis longus and thenar intrinsic muscles. These types of fracture-dislocations are prone to slipping and are not stable; therefore, it should be treated more aggressively (2). Inadequate placement and replacement can lead to posttraumatic arthritis and disability. In Bennett fracture-subluxations, if the joint stepping is greater than 2 mm, percutaneous fixation with a K-wire is performed after closed correction and replacement (3).